Enhancing postpartum depression screening and management in tertiary care: a comprehensive approach - Jayaraman, Lokeshwari; Dev, Sathish; Suganthavalli; Kumar, Amar Nagesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Postpartum depression (PPD) is a significant public health issue affecting a substantial number of new mothers. Despite its prevalence, PPD often goes undiagnosed and untreated due to inconsistent screening practices and lack of standardized management protocols. This research project aimed to enhance the screening and management of PPD in a tertiary care hospital through the implementation of a comprehensive and evidence-based approach. Methods: The study was conducted in several phases: assessment of current practices, development and implementation of an enhanced screening protocol, systematic screening to assess prevalence, improvement of early detection and referral systems, evaluation of management strategies, awareness and education campaigns, and follow-up studies. Data collection involved surveys and interviews with healthcare providers, screening of 500 postpartum women using the Edinburgh Postnatal Depression Scale (EPDS), and patient satisfaction surveys. Statistical analyses were performed to determine PPD prevalence and evaluate the effectiveness of management strategies. Results: The assessment of current practices revealed that only 35% of healthcare providers routinely screened for PPD, with no standardized protocol. The enhanced screening protocol, integrated into routine care, achieved a 100% screening rate among postpartum women. The prevalence of PPD was found to be 15%, with higher rates among women with low socio-economic status and lack of social support. The streamlined referral process ensured that all women who screened positive were referred to mental health services, with an 87% follow-up attendance rate. Management strategies, including cognitive-behavioral therapy (CBT) and pharmacotherapy, led to significant improvement in 85% of women receiving CBT and 92% receiving both CBT and medication. Patient satisfaction surveys indicated a 90% satisfaction rate with the screening and management process. Long-term follow-up studies showed sustained improvement in 85% of women at six months postpartum. Conclusions: The comprehensive approach to PPD screening and management significantly improved detection, referral, and treatment outcomes in a tertiary care hospital. Standardized screening protocols, effective referral systems, and integrated care models are essential for addressing PPD. The project’s success highlights the importance of early detection, targeted interventions, and continuous care to promote maternal mental health and well-being. Future efforts should focus on refining and expanding these protocols to ensure sustained improvements and support for postpartum women.